Natural capital in the alternative theories of economic growth - Slobodan Cvetanović; Andrea Panić Andrejević (Economic Themes, 2024)
In economic science, the content coverage and characteristics of natural capital as a determinant of economic growth were often discussed by affirming the paradigm of sustainability at the end of the previous century. The largest number of researchers supported the thesis that economic growth should be sustainable, which means that it does not imply excessive use of natural capital (natural resources and the absorption and regenerative capacity of ecological systems) per unit of newly created value. During the previous years, new growth concepts known as Green growth, Degrowth, Post growth and Doughnut appeared in the explanations of natural capital as a limiting determinant of economic growth. At the core of these concepts is a sharp opposition to the views of neoclassical economists on the possibility of an unlimited increase in economic activities. Among other things, this happens due to the fact that natural capital, as one of the basic drivers of economic growth, is limited and cannot be substituted by other production factors.
Keywords: O44; Q01; 330; Natural capital; Green growth; Degrowth; Post growth; Doughnut